Taxonomic revision of Cylindera Westwood, 1831 subgenus Parmecus Motschulsky, 1864 stat. rest., stat. nov. (Coleoptera: Carabidae: Cicindelinae) with the description of one new species from Yunnan Province, China - Matalin, Andrey V. (Zootaxa, 2019)
Within the Asiatic tiger beetle fauna, Parmecus Motschulsky, 1864 stat. rest., stat. nov., is reestablished as a subgenus of Cylindera Westwood, 1831 with Cylindera (Parmecus) dromicoides (Chaudoir, 1852), as its type species, and the lectotype and paralectotypes of Cicindela dromicoides Chaudoir, 1852 are designated as well. Two other species are included, Cylindera (Parmecus) armandi (Fairmaire, 1886), from the Himalayan Region, and Cylindera (Parmecus) mosuoa, sp. nov., from Yunnan, China. Cylindera (Parmecus) as a subgenus is characterized, a key to identify its species is provided, and its species composition is discussed. Cylindera (Parmecus) dromicoides (Chaudoir, 1852) is newly recorded from Pakistan and the Indian state of Jammu and Kashmir, while Cylindera (Parmecus) armandi (Fairmaire, 1886) is recorded for the first time from the Chinese province of Sichuan. The records of C. armandi from Bhutan, as well as C. dromicoides from Yunnan Province (China) are rejected due to erroneous identifications.